Sol-gel auto combustion synthesis of Al3+-Gd3+ ions co-doped cobalt ferrite nanoparticles for nanoelectronics applications - Raut, Vaibhav K.; Somvanshi, Sandeep B.; Dawi, Elmuez A.; Birajdar, Chandrakant T. (Journal of sol-gel science and technology, 2024)
This study focused on investigating cobalt ferrite nanoparticles doped with trivalent Al 3+ and Gd 3+ ions across compositions ranging from CoFe 2-2x Al x Gd x O 4 (x = 0.00, 0.02, 0.04, 0.06, 0.08). The nanoparticles were synthesized using the sol-gel auto-ignition method with citric acid as a chelating agent. Structural analysis via Rietveld-refined X-ray diffraction confirmed the formation of single-phase nanoparticles with a cubic spinel structure. Morphological examination through scanning electron microscopy revealed spherical-shaped grains. Elemental analysis using energy-dispersive X-ray analysis indicated consistent composition and high purity. Infrared spectra analysis verified the presence of characteristic modes typical of spinel ferrite structures. Magnetic properties assessed by vibrating sample magnetometry demonstrated soft magnetic behavior with lower coercivity. DC electrical resistivity measurements indicated a decrease in resistivity with increasing Al 3+ -Gd 3+ co-doping, while dielectric studies showed enhanced properties in this regard. Overall, the findings suggest that these co-doped cobalt ferrite nanoparticles hold promise for applications in magneto-electronic devices. Graphical Abstract Highlights CoFe 2 O 4 nanoparticles co-doped with Al 3+ and Gd 3+ were synthesized using sol-gel auto-combustion. SEM revealed spherical nanoscale grains, and XRD showed increased lattice constants with co-doping. Saturation magnetization and magneton number decreased with higher co-doping levels. Co-doping improved electrical conductivity and showed typical frequency-dependent dielectric behavior. These nanoparticles are promising for magneto-electronic and high-frequency applications.